Good Hospitals - Kaebnick, Gregory E. (The Hastings Center report, 2015)
The two articles in this issue of the Report consider different ways that hospitals' organizational failings can be masked by ethics talk. In the lead article, Ann Hamric, John Arras, and Margaret Mohrmann take a critical look at the increasingly popular view that courage is a vital part of the moral armamentarium of health care professionals. It's easy to overemphasize and distort this point, they argue. Alexandra Junewicz and Stuart Youngner have a somewhat similar take on patient satisfaction surveys, which are now in widespread use at most hospitals. Surveys are valuable, say Junewicz and Younger, but it is very easy to make too much of them and to misuse them.